The use of cost information inthe reports and financial analyzes of hospital - Chluska, Jolanta; Szewieczek, Aleksandra (Wykorzystanie informacji kosztowych w raportach i analizach finansowych szpitala, 2018)
Evaluation of hospital standing is one of the tasks of the funding bodies of hospitals. The evaluation is made based on the indices of measurements specified in the Ordinance of the Minister of Health. These indices relate to various areas of hospital activities, including their financial results. There are no indices based directly on costs. The aim of the study is to identify the role of costs as a basis for the evaluation of economic and financial status of hospital. The research hypothesis states: it is necessary to increase the role of hospital operating costs in the assessment of their economic-financial condition. The research tools included the analysis of legal acts, related literature and practical examples of hospital reports on economic and financial situation of independent public health care institutions. Final conclusions were developed using the method of deduction and synthesis
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 524; s. 22-34
Keywords: hospital; costs; analysis; evaluation of economic and financial standing of hospitals; szpital; koszty; analiza; ocena kondycji ekonomiczno-finansowej szpitali